Participant observer an autobiography - Whyte, William Foote 1914- (ILR Press, 1994)
What would happen if a social scientist saw himself not as an outsider but as a participant, engaging in the situations he studied and acting to change the course of events? The distinguished career of William Foote Whyte as an activist scholar provides a rich and complex answer to that question. Participant Observer is Whyte's own story. He takes us to worksites from Boston's North End in the early forties to Spain and Peru in the seventies to Jamestown, New York, in the eighties. Along the way, we see the development of his thinking and the spread of his influence into fields as disparate as social psychology, industrial relations, and agricultural development. While it documents a remarkable career, Participant Observer is also a personal chronicle. Whyte reflects with candor and sometimes great amusement on the years of his childhood, his academic education, and his marriage. He also describes being stricken with polio and recounts how he and his family worked to circumvent the handicaps the disease dealt him. Beginning with his study of neighborhood gangs in Boston's North End and moving into such diverse workplaces as the oil fields of Oklahoma, the dining rooms of Stouffer's, and rural villages in Peru, Whyte's research has focused on connections between social organization and human performance. Whyte listened to what workers told him, gave their views weight in his recommendations to decision makers, and eventually became a powerful voice for greater worker participation and workplace democracy. His work is a model for the social sciences and his story should be read by any serious student of them.